Konfliktas kaip tiesos sąlyga – G. Vattimo ir J. D. Caputo = Conflict as a Condition of Truth : G. Vattimo and J. D. Caputo - Okunauskas, Aurimas (Religija ir kultūra, 2014)
Through the writings of Gianni Vattimo and John D. Caputo this text attempts to discover the boundaries of the concept of truth and the meaning of truth for postmodern thinking. It is important to both authors to establish a distance from truth as adaequatio, because they both adopt a position that an authentic response to the reality of a multicultural contemporary world does not permit subscribing to such a conception of truth. The text highlights the new status of truth in a postmetaphysical discourse, namely its impossible character arising from the ethical-practical role that truth assumes in attempts to keep the dialogue open, which is, in turn, an attempt to avoid the slide back into metaphysics. Openness to truth is interpreted through the state of conflict, which occurs when the questioning turns to the very possibilities of dialogue and conflict then shows itself to be essential in avoiding the closure of the question of truth (especially in the fields of politics and science). Science is employed as a paradigmatic example of a closed, self-sufficient rational system, focusing on its hermeneutical roots.